تطبيقات الذكاء الاصطناعي وأثرها في تحقيق الميزة التنافسية: دراسة على البنوك الأردنية - العبداللات، عبدالفتاح زهير عبدالفتاح (جامعة مؤتة, 2020)
هدفت الدراسة التعرف إلى أثر تطبيق الذكاء الاصطناعي في تحقيق الميزة التنافسية، والتعرف على واقع تطبيق الذكاء الاصطناعي لدى البنوك الأردنية، وطبقت الدراسة على عينة مكونة من 330 موظف تم اختيارهم بطريقة عشوائية متساوية من 16 بنكا أردنيا بفروعها المنتشرة، وقد تم استخدام الانحدار الخطي المتعدد لاختبار فرضيات الدراسة. وقد خلصت الدراسة إلى أن توسع البنوك في تطبيقات الذكاء الاصطناعي يسهم في تحقيق الميزة التنافسية للبنوك من خلال تخفيض كلفة الخدمة المصرفية، وتعزيز جودتها، وزيادة الحصة السوقية للبنوك، وإلى وجود تفاوت في تأثير تطبيقات الذكاء الاصطناعي في تحقيق الميزة التنافسية، إذ تبين من نتائج الدراسة أن بصمة العميل، والدردشة المصرفية هي الأكثر تأثيرا، حيث فسرت معا ما يقارب (48%) من التغير في الميزة التنافسية. وقد أوصت الدراسة بأهمية توسع البنوك في الأردن في تطبيقات الذكاء الاصطناعي وذلك لأهميتها في تحقيق الميزة التنافسية للبنوك، وخصوصا تخفيض تكاليف الخدمة المصرفية المقدمة مما يسهم في زيادة أرباحها.
The study aimed at identifying the impact of the artificial intelligence applications in achieving the competitive advantage, and recognizing the reality of applying artificial intelligence applications in Jordanian banks. The study was applied to a sample of 330 employees who were randomly selected from 16 Jordanian banks with branches scattered across the country, and multiple linear regression was used to examine the study hypotheses. The study concludes that banks expansion in artificial intelligence applications can achieve the competitive advantage of banks through reducing the banking service cost, enhancing their quality, increasing the market share of banks, and disparate impact in artificial intelligence applications to get the competitive advantage. The results of the study revealed that the customer print and the chatbot are the most influential on achieving the competitive advantage as they explain nearly (48%) of the change in the competitive advantage. The study recommended emphasizing the importance of banks expansion in Jordan using artificial intelligence applications, as it has been significant in achieving the competitive advantage of banks, particularly reducing the banking service cost provided which would maximize its profits.
Keywords: تكنولوجيا المعلومات -- الذكاء الاصطناعي -- الميزة التنافسية -- الخدمات المصرفية -- الأردن